2020
DOI: 10.1007/s11160-020-09603-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet radiation (UVR) on the life stages of fish

Abstract: Current levels of Ultraviolet Radiation (UVR) represent a significant threat to many fish species. The first studies on the effects of UVR on organisms were performed on fish at the beginning of the twentieth century, and the topic has been progressing continuously until the present. Here, we review the reported harmful effects of ultraviolet B (UVB) and A (UVA) radiations in fish at different lifecycle stages, including embryo, larvae, juveniles and adults. The most evident negative effects during the early d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 180 publications
2
28
1
Order By: Relevance
“…9 ). Negative effects range from developmental abnormalities, to decreases in growth and body condition, to lesions in skin, eyes, as well as in many other organs, and even death [ 263 ]. Often, the more transparent, younger life-history stages are vulnerable to UV-induced damage, in particular because they typically inhabit shallow, warmer surface waters to increase developmental rates.…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 ). Negative effects range from developmental abnormalities, to decreases in growth and body condition, to lesions in skin, eyes, as well as in many other organs, and even death [ 263 ]. Often, the more transparent, younger life-history stages are vulnerable to UV-induced damage, in particular because they typically inhabit shallow, warmer surface waters to increase developmental rates.…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…Often, the more transparent, younger life-history stages are vulnerable to UV-induced damage, in particular because they typically inhabit shallow, warmer surface waters to increase developmental rates. The skin and gills are the most highly exposed and most likely sites of damage by UV-B radiation, although immune suppression, visual impairment, and other damage is commonly reported in both natural populations and hatchery-raised fish [ 263 ]. The corresponding reductions in fish survival, growth, and reproduction have as yet unquantified implications for the yield of commercial and recreational fisheries that provide critical supplies of food to much of the world’s population (SDG 2.4).…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, cortisol has been shown to modulate the immune response [ 146 , 171 , 172 , 173 ] and decrease club cell density [ 146 ]. Cortisol levels were also increased upon exposure to UV rays [ 19 , 20 ], and UV rays can affect other aspects of fish’s immune systems [ 174 ]. Clearly, further studies are needed to establish the mechanistic links and signaling pathways.…”
Section: An Overview Of the Immune System In Fishesmentioning
confidence: 99%
“…UVR are not only dangerous for photosynthetic organisms but they can cause damage to a wide range of living organisms, from bacteria to higher vertebrates, and their effects can change depending on other environmental conditions [ 35 ]. For instance, UVR negatively affects the viability and development of invertebrates and fish, whose early developmental stages are generally more sensitive [ 36 , 37 ]. Indeed, CPDs formation in sea urchin embryos and larvae inhibits their development, decreasing population survival and fitness [ 38 ].…”
Section: Photo-damage/-protection Mechanisms In Marine Organismsmentioning
confidence: 99%